2009
DOI: 10.1007/s00268-009-0099-y
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion of the Hamstring Muscle Group: A Follow‐Up of 6 Adult Non‐Athletes with Early Operative Treatment: A Brief Report

Abstract: Background Complete proximal avulsions of the ham-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Nonetheless, one previous study utilizing the HHS demonstrated excellent results in all 6 patients undergoing surgery for a proximal hamstring rupture. 20 The MRI findings in postsurgical patients in our cohort demonstrated a 100% healing rate. At a mean follow-up of 36 months after surgery, the hamstring muscle complex was noted to be attached to the ischial tuberosity with anchors in all cases.…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, one previous study utilizing the HHS demonstrated excellent results in all 6 patients undergoing surgery for a proximal hamstring rupture. 20 The MRI findings in postsurgical patients in our cohort demonstrated a 100% healing rate. At a mean follow-up of 36 months after surgery, the hamstring muscle complex was noted to be attached to the ischial tuberosity with anchors in all cases.…”
Section: Discussionmentioning
confidence: 95%
“…A complete rupture is defined as the tearing of all three tendons (biceps femoris, semitendinosus, and semimembranosus) from the ischial tuberosity 7,8 . Since the initial report of this entity in adults 9 , the literature has supported early surgical repair in acute tears [10][11][12][13][14][15][16][17][18][19][20][21][22] . A delay in surgical management results in residual loss of function 20 , persistent pain and weakness with delay in return to sports 8,11,15,21,23 , and late sciatic nerve palsy 24 .…”
mentioning
confidence: 99%
“…Most studies were either retrospective case series or retrospective case reports; two retrospective reviews of prospectively collected case series were identified 24 25. Of the 22 studies, 17 studies2–4 10 11 13 14 16–18 20–25 reported on return to sport and of the 22 studies, 13 studies1–3 11–13 15 17–19 22 24 26 reported on patient satisfaction with 10 studies2 3 11–13 17–19 22 24 reporting on both outcomes. Four studies3 10 11 22 identified non-operative management of acute hamstring avulsions and 181 2 4 12–26 studies identified operative management of acute hamstring injuries, with 1 study22 detailing operative and non-operative management.…”
Section: Resultsmentioning
confidence: 99%